(untitled) (The Research of Medical Science Review, 2025)
Objective: To investigate corneal topographical and biomechanical parameters in mothers of children diagnosed with Down’s syndrome (DS), and to compare them with mothers of children without Down’s syndrome, in a tertiary care hospital in Pakistan. Study design: A comparative cross-sectional study. Place and Duration of study: Armed Forces Institute of Ophthalmology, Rawalpindi, Pakistan, from June 2024 to November 2024 Methodology: A comparative analysis was carried out, 188 eyes of 94 patients were studied, forty-seven in Group-A (mothers of Down’s syndrome children) and forty-seven in Group-B (mothers of normal children). In this study, the corneal topographical and biomechanical parameters of mothers of children diagnosed with Down’s syndrome were studied and compared to their age matched counterparts. Results: The participants average age was 35.8 years in Group-A and 33 years in Group-B. Statistically significant differences were observed between group means for flat simulated keratometry K1 (p value 0.00), steep simulated keratometry K2 (p value 0.00), K maximum (p value 0.024), Belin Ambrosio Enhanced Ectasia Display (p value 0.002) and Topographical biomechanical index (p value 0.02) Conclusion: Our findings reveal a higher prevalence of deranged keratoconus parameters in Group A than in Group B, pointing toward a milder, subclinical presentation of the condition.